Midtrimester isolated short femur and perinatal outcomes: A systematic review and meta‐analysis. (31st October 2018) - D'Ambrosio, Valentina; Vena, Flaminia; Marchetti, Claudia; Di Mascio, Daniele; Perrone, Seila; Boccherini, Chiara; Pizzuti, Antonio; Benedetti Panici, Pierluigi; Giancotti, Antonella
Abstract: Introduction: Fetal femur length below the expected value has been described as a marker of aneuploidy, skeletal dysplasia, intrauterine growth restriction and small‐for‐gestational‐age neonate. The aim of this systematic review and meta‐analysis was to evaluate the strength of association between isolated short femur length and intrauterine growth restriction or small‐for‐gestational‐age, and perinatal adverse outcomes. Material and methods: PubMed, EMBASE and Medline were searched from the inception of each database to May 2018. Selection criteria included prospective and retrospective cohort studies of singleton pregnancies between 18 and 28 weeks of gestation, with sonographic finding of isolated short femur length, without any structural chromosomal abnormality. The meta‐analysis was performed by computing odds ratios using both fixed and random‐effects models. Quality assessment of the included studies was performed using the Newcastle‐Ottawa Scale. Results: Six studies including 3078 cases of isolated short femur length (study group) and 222 303 normal femur length (control group) were included. The prevalence of intrauterine growth restriction or small‐for‐gestational‐age in the study group was 14.2%, compared with 5.2% in the control group (odds ratio of 4.04, 95% confidence interval 3.63‐4.50). Isolated short femur length was associated with a higher incidence of low birthweight (study group: 22.10% vs control group: 8.57%, odds ratio 3.24, 95% confidence interval 2.34‐4.48), Apgar <7 at 5 minutes (study group: 3.98% vs control group: 1.79%, odds ratio 3.56, 95% confidence interval 1.87‐6.77), preterm birth (study group: 12.16% vs control group: 8.16%, odds ratio 3.09, 95% confidence interval 1.57‐6.08), fetal death (study group: 1.83% vs control group: 0.44%, odds ratio 6.48, 95% confidence interval 3.70‐11.35) and neonatal intensive care unit admission (study group: 15.34% vs control group: 14.81%, odds ratio 2.11, 95% confidence interval 0.56‐7.93). Conclusions: There is a significant association between isolated short femur length and intrauterine growth restriction or small‐for‐gestational‐age and poor perinatal outcome.